PENGEMBANGAN HOME ECONOMICS DI SMA - Ahmad Chafid Alwi; Sri Umi Mintarti Widjaja; Sunaryanto Sunaryanto (Pascasarjana Universitas Negeri Malang, 2017)
The purpose of this study was to create and measure feasibility test of Home Economics in high school. This research method using the 4D model (Define, design, develop, and disseminate). The results of the content validation test showed 92% (very decent), media validation test results showed 73% (feasible with minimal revision), the test results of 93% of personal had a (very decent) and the limited test group had a 91% (very decent). Based on these results, the development of Home Economics in high school which packed into the teacher guide books and teaching materials are very decent student. Penelitian ini bertujuan untuk menghasilkan dan menguji kelayakan Home Economics di SMA. Metode penelitian ini menggunakan model 4D (Define, design, develop, and disseminate). Hasil uji validasi isi menunjukkan 92% (sangat layak), hasil uji validasi media menunjukkan 73% (layak dengan sedikit revisi), uji perorangan memiliki hasil 93% (sangat layak) dan pada uji kelompok terbatas memiliki 91% (sangat layak). Berdasarkan hasil tersebut maka pengembangan Home Economics di SMA yang dikemas kedalam buku panduan guru dan bahan ajar siswa sangat layak.